Analytical theory for fatigue crack propagation rates of mixed-mode I–II cracks and its application. (February 2019) - Qi, S.; Cai, L.X.; Bao, C.; Chen, H.; Shi, K.K.; Wu, H.L.
Highlights: A low-cycle fatigue crack propagation (LCF-FCP) rate model is proposed. This model applies to propagation of plane-stress mixed-mode I–II cracks. A model for the J e integral of mixed-mode I–II CTS specimens is proposed. These models yield good agreement with experimental crack propagation results. Abstract: The Manson–Coffin law for the low-cycle fatigue (LCF) of a representative volume element (RVE) and fatigue crack propagation (FCP) rate of cracked components can characterize material fatigue resistance. This paper proposes an LCF–FCP model for predicting the FCP rate of plane-stress mixed-mode I–II cracks. A semi-analytical model is also proposed for the J e integral of mixed-mode I–II compact tension shear (CTS) specimens based on energy equivalence method. The combination of these two models predicted the FCP rates of CTS specimens made from 30Cr2Ni4MoV rotor steel with mixed-mode I–II cracks and subjected to four different loading angles. The theoretical results were consistent with the experimental results.